Auditory Stream Segregation and Selective Attention for Cochlear Implant Listeners: Evidence From Behavioral Measures and Event-Related Potentials - Paredes-Gallardo, Andreu; Innes-Brown, Hamish; Madsen, Sara M. K.; Dau, Torsten; Marozeau, Jeremy (Frontiers in Neuroscience, 2018)
The role of the spatial separation between the stimulating electrodes (electrode separation) in sequential stream segregation was explored in cochlear implant (CI) listeners using a deviant detection task. Twelve CI listeners were instructed to attend to a series of target sounds in the presence of interleaved distractor sounds. A deviant was randomly introduced in the target stream either at the beginning, middle or end of each trial. The listeners were asked to detect sequences that contained a deviant and to report its location within the trial. The perceptual segregation of the streams should, therefore, improve deviant detection performance. The electrode range for the distractor sounds was varied, resulting in different amounts of overlap between the target and the distractor streams. For the largest electrode separation condition, event-related potentials (ERPs) were recorded under active and passive listening conditions. The listeners were asked to perform the behavioral task for the active listening condition and encouraged to watch a muted movie for the passive listening condition. Deviant detection performance improved by increasing electrode separation between the streams, suggesting that larger electrode differences facilitate the segregation of the streams. Deviant detection performance was best for deviants happening late in the sequence, indicating that a segregated percept builds up over time. The analysis of the ERP waveforms revealed that auditory selective attention modulates the ERP responses in CI listeners. Specifically, the responses to the target stream were, overall, larger in the active relative to the passive listening condition. Conversely, the ERP responses to the distractor stream were not affected by selective attention. However, no significant correlation was observed between the behavioral performance and the amount of attentional modulation. Overall, the findings from the present study suggest that CI listeners can use electrode separation to perceptually group sequential sounds. Moreover, selective attention can be deployed on the basis of the resulting auditory objects, as reflected by the attentional modulation of the ERPs at the group level.